The Relationship Between Sleep Quality and Stress Levels in Nursing Professional Study Program Students at Muhammadiyah University of Jember - Saiful Rizal; Sofia Rhosma Dewi; Yeni Suryaningsih (Penerbit Hellow Pustaka, 2025)
Background: The final period of the Nursing professional study is a critical period for students, because this period is full of processes that require students to complete their education on time. Students often experience stress in completing nursing professional tasks, both from within and outside themselves. Internal stressors faced by Thesis students such as difficulty in obtaining references, limited research time, repeated revision processes, difficulties in finding themes, titles, samples, and measuring tools for the final assignment. Meanwhile, stressors originating from outside such as limited funds, busy and difficult to meet supervisors, long feedback from supervisors, and lack of consultation with supervisors when completing the Nursing Science study program cause students to experience stress which causes sleep pattern disorders in students Method: : This study design uses a correlational approach with a cross-sectional approach. The population in this study was an average of 106 people formulated by the Slovin formula to 84 people. The sampling used was non-probability sampling with a quota sampling technique. Data collection on sleep quality with stress levels used a Likert scale. Data analysis used Spearman Rho with the provision of α ≤ 0.05. Results: It is known that in the University of Muhammadiyah Jember Nursing Profession study program, there are 54 people (64.3%) who experience adequate sleep quality and moderate stress levels of 54 people (64.3%). Based on statistical tests using Spearman-Rho, the results obtained p-value = 0.000 (α <0.05) with a correlation of 0.820. This indicates that H1 is accepted, thus there is a relationship between variables x and y which means there is a relationship between sleep quality and stress levels of students with a strong relationship strength. Conclusion: There is a relationship between sleep quality and stress levels in students of the Nursing Profession study program, University of Muhammadiyah Jember.